Lake pulses driven by glacier melting and climate variability - Songtao Ai; Shoukat Ali Shah; Yi Cai; Jiajun Ling; Xinde Chu; Shijin Wang; Yuande Yang; Runchuan Ouyang; Jiachun An; Wolfgang Rack (Scientific Reports)
Abstract The Tibetan Plateau is home to numerous glaciers that are important for freshwater supply and climate regulation. These glaciers, which are highly sensitive to climatic variations, serve as vital indicators of climate change. Understanding glacier-fed hydrological systems is essential for predicting water availability and formulating climate adaptation strategies. This study investigated the dynamic fluctuations in the water level of the Blue Moon Lake Valley (BMLV), supplied by meltwater from Baishui River Glacier No. 1 on Yulong Snow Mountain. We focused on the lake pulse phenomenon—subtle yet significant water level fluctuations that have often been overlooked in prior research. By employing fast Fourier transform (FFT), multivariate regression (MVR), and random forest (RF) models, we examined the interactions among glacier melt dynamics, climatic variables, and hydrological responses. Our analysis indicates that the rate of change (ROC) in the water level fluctuates between − 0.006 and 0.01 m/min, with a median ROC of − 7.24E−06 m/min, highlighting the significant variability influenced by glacier melt and precipitation. The maximum cumulative sum (CS) value of 0.09 m suggests a net increase in the water level, predominantly due to increased precipitation, decreased evaporation, and increased glacier melting. We demonstrate that temperature critically influences glacier melt rates and water level variations, alongside solar radiation, rainfall, atmospheric pressure, and wind speed. The ROC of Baishui River Glacier No. 1 melt ranges from − 0.0016 to 0.0015 m/min, reflecting substantial variation with significant downstream implications for water availability during dry seasons. The mean interval between consecutive glacier melt peaks is approximately 2.87 h, with a strong positive linear trend R2 = 0.99, indicating frequent melt events. Conversely, water level peaks occur approximately every 6.5 h, with a strong positive trend R2 = 0.99, indicating a slower recurrence rate. The transit time for meltwater from Baishui River Glacier No. 1 to BMLV is estimated at approximately 4.16 h. Additionally, we quantify the water flux from BMLV across various timescales, highlighting the substantial contribution of glacial meltwater. This novel study systematically examines the hydrological dynamics of BMLV. This study has the potential to reveal broader implications for water resource management, ecosystem dynamics, and climate change adaptation in regions dependent on glacier-fed lakes.